Katechizm biblijny Kościoła kartagińskiego - Tomasz Kaczmarek (Polonia Sacra)
The topic for discussion of this thesis is Ad Quirinum, the second tome of st. Cyprian’s work, the bishop of Carthagina (210–258) which can be thought of as a remarkable biblical catechism. This book, composed of thirty Christological thesis together with corresponding biblical citations, is dedicated to “the mystery of Christ” (sacramentum Christi) understood as concise presentation of salvation economy where Christ is its centre and the interpretative key for the Bible. This image is that interesting because it is the only pre- Nicean Christology compendium of this type, which directly introduces us to theological thought preceding a very difficult for Christianity trinitian controversy.